An Analysis of Teacher’s Discourse Markers in SMK N 3 Teluk Kuantan - Pertiwi, Anggun; Ratmanida, Ratmanida (Journal of English Language Teaching, 2024)
This study examines the type of discourse markers based on Fang and Carter theory (2007) in the teachers’ talk and the reason why teachers used dominant discourse markers at SMK N 3 Teluk Kuantan. The research  design  of this study is descriptive qualitative. The data is collected though observation, recording and interview. The subjects of this research are two English teachers at SMK N 3 Teluk Kuantan. The result showed that there were four type discourse markers used by teachers, namely, interpersonal, referential, structural and cognitive. Interpersonal markers were the dominant posed  by teachers in the teaching and learning process which was 60,00%, 22,31% referential, 15,94% structural and 1,73% cognitive. The teachers used dominant markers for providing students with effective instruction and guidance especially for taking student’s attention, increasing their confidence in the classroom interaction, as fillers also highlight the key of conversation and measuring students’ understanding. Keywords:Discourse markers, teacher’s   talk, classroom interaction